The Seasonal Variations of Planktonic and Epilithic Diatoms in Kalecik Reservoir (Elazig, Turkey) - Sonmez, Feray (Medwell Online, 2011)
In the study, the planktonic and epilithic diatoms were studied at four stations selected on Kalecik reservoir between March and October 2010. Sampling was performed monthly. Some physical and chemical characteristics (Water temperature, electrical conductivity, pH and concentrations of dissolved oxygen and total hardness) of the reservoir were measured throughout the duration of the study. Of the 41 diatom taxa identified during the study. The seasonal variations in these diatoms were examined together with their physical and chemical characteristics and the results of this examination were compared with the results of previous studies carried out in reservoirs.
Keywords: Kalecik reservoir; diatom; epilithon; plankton; seasonal variation; Elazig